HUBUNGAN DEPRESI DENGAN INSOMNIA PADA LANSIA DI UPT PELAYANAN SOSIAL TRESNA WERDHA (PSTW) JEMBER: The Relationship Between Depression and Insomnia in The Elderly at the UPTD Social Service Tresna Werdha (PSTW) Jember - Muthoharoh, Nur Imamah; Dewi , Sofia Rhosma; Suryaningsih, Yeni (Forind Press, 2024)
Depression is a common mental disorder characterized by symptoms such as feelings of sadness, loss of pleasure or interest, guilt, or low self-worth. Depression can occur acutely or chronically, leading to disruptions in an individual's daily activities. The aim of this study is to investigate the relationship between depression and insomnia among the elderly at the Social Services Unit for Elderly (UPT Pelayanan Sosial Tresna Werdha, PSTW) in Jember. This study employed a correlational research design with a Cross-Sectional approach. The sampling technique utilized purposive sampling. Data collection was conducted using a questionnaire. The study found that the majority of elderly individuals experienced depression, 38 (56.7%), and the majority experienced insomnia, 57 (85.7%). Statistical tests showed a p-value of 0.020 < 0.05 using Pearson Correlation test. These results indicate that the alternative hypothesis (H1) is accepted with a correlation coefficient (r) = 0.873, indicating a significant relationship between depression and insomnia at the Social Services Unit for Elderly (UPT Pelayanan Sosial Tresna Werdha, PSTW) in Jember. Healthcare professionals, especially nurses, can help provide education on how to manage depression in the elderly.